Assessing different patterns of laser welding with Nickel-Chromium (Ni-Cr) alloy for structures applicable to fixed prosthesis - Martins, Jarbas Eduardo; Bastos Neto, Fábio V.R.; Duarte, Danilo Antônio; Araki, Ângela Toshie (Brazilian Dental Science, 2017)
Among all desired requirements to dental prosthesis, marginal adaptation and passive fit are the most important. In some cases, in order to achieve these goals, it is necessary to cut and weld the teeth / implant-supported framework. Nowadays, the laser welding process shows a great advantage in comparison to other methods. The aim of this study was to evaluate the optimal laser welds point that is more appropriate to Ni-Cr prosthetic framework. A total of 60 specimens of Ni-Cr (35 mm x 4 mm) were designed and welded using a Nd:YAG laser device model EV 900. They were fixed in a metal piece 0.27 mm between the ends to be welded. All specimens were welded with 21 laser pulses diametrically opposed (frequency of 1.0Hz, load time 3.0 ms and 0.5 mm of diameter pulse). They were divided into three groups according to the electric current of the laser weld: A – 180A; B – 200A and C – 220A. To determinate the flexural mechanic strength, all specimens were submitted to a three-point bending test. The results obtained were: Group A = 553 Mpa; B = 751 Mpa and C = 802.1 Mpa. The control group was 1040.9 Mpa. ANOVA and Tukey’s test were performed and statistical significance differences were observed between group A and B as well as between group A and C. However, no significant difference was observed between B and C.